Application of Local Hypothermia for Induced Abortion in 2nd Trimester - Saltovsky, A. V. (Problems of Cryobiology and Cryomedicine, 2005)
The application results of hypogastric area cooling for induced abortion at late terms are presented. We examined 112 women in pregnancy term from 16 to 26 weeks. The obtained clinical and laboratory data testify to the efficiency and advantages of this method over the current ones.